Associated adverse outcomes with tumor treating fields when combined to temozolomide versus temozolomide alone for the treatment of glioblastoma: a meta-analysis of randomized trials - Yuanyuan Chen; Yan Chen; Hong Zhen; Danhua Lou (Egyptian Journal of Neurosurgery)
Abstract Background Glioma is a brain tumor and glioblastoma represents its most common type, accounting for almost 40% of primary tumors of the central nervous system, and is associated with the worst prognosis. Glioblastoma remains one of the major challenges in neurooncology. Recently, the Food and Drug Administration (FDA) has approved tumor treating fields (TTF) for the treatment of glioblastoma. In this analysis, we aimed to systematically assess the adverse outcomes associated with TTF when combined to temozolamide versus temozolamide alone for the treatment of glioblastoma. Methods MEDLINE (subset PubMed), EMBASE, Web of Science, Cochrane databases, Google scholar, and http://www.ClinicalTrials.gov were searched for publications comparing TTF in combination with temozolomide versus temozolomide alone for the treatment of glioblastoma. The adverse outcomes were considered as the endpoints in this analysis. The statistical analysis was carried out by the latest version of the RevMan software (version 5.4). Risk ratios (RR) with 95% confidence intervals (CI) were used to represent the data following assessment. A random effect model was used during the statistical analysis. Results A total number of 994 participants were included in this analysis whereby 572 participants were assigned to TTF + temozolomide, whereas 422 participants were assigned to temozolomide alone. All the studies were randomized trials. The majority of the participants were males (68.0–75.0%) with a mean age of the varying from 54.0 to 69.0 years. Results of this analysis showed that TTF in combination with temozolomide was not associated with significantly higher adverse outcomes related to blood and lymphatic system disorders (RR:0.87, 95% CI 0.30–2.48; P = 0.79), gastrointestinal disorders (RR: 0.83, 95% CI 0.14–4.72; P = 0.83), general deterioration and malaise (RR: 1.43, 95% CI 0.90–2.25; P = 0.13), infections and infestations (RR: 1.21, 95% CI 0.33–4.45; P = 0.78), injury/poison and procedural complications (RR: 1.78, 95% CI 0.88–3.61; P = 0.11), metabolic and nutritional disorders (RR: 0.61, 95% CI 0.34–1.08; P = 0.09), central nervous system disorders (RR: 1.14, 95% CI 0.89–1.46; P = 0.31), musculoskeletal and connective tissue disorders (RR: 0.99, 95% CI 0.48–2.07; P = 0.99), respiratory/thoracic/mediastinal disorders (RR: 0.85, 95% CI 0.44–1.62; P = 0.62), and psychiatric disorders (RR: 1.27, 95% CI 0.42–3.79; P = 0.67). Similar adverse effects were observed. Conclusion TTF in combination with temozolomide was not associated with significantly worse adverse outcomes for the treatment of patients with glioblastoma. Hence, future trials should focus on the cost-effectiveness of TTF for the treatment of glioblastoma.